2019
DOI: 10.3390/geosciences10010010
|View full text |Cite
|
Sign up to set email alerts
|

Negative Anomalies of the Earth’s Electric Field as Earthquake Precursors

Abstract: Anomalies of the electric field potential gradient have been observed in the near-ground air before earthquakes in different regions of the world. Such anomalies are likely caused by radon air ionization. In this study, the impact of this precursor was estimated according to continuous observations of the electric field in Kamchatka in 1997–2002.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 15 publications
(19 reference statements)
0
3
0
2
Order By: Relevance
“…Since the duration of the electric field disturbance was approximately 2 minutes, according to the satellite velocity of 8 km/s, the horizontal spatial scale was 900 km. Along with the satellite monitoring of the ionosphere over seismically active regions, the behavior of the electric field on the Earth's surface before earthquakes is analyzed [Vershinin et al, 1999;Hao et al, 1998;2000;Rulenko, 2000;Smirnov, 2020]. It was shown that during the preparation of an earthquake, short local bursts of an electric field of large amplitude up to several kV/m with a duration of a few to tens of minutes occur.…”
Section: Analysis Of Results Of Observations Of the Electric Field In...mentioning
confidence: 99%
“…Since the duration of the electric field disturbance was approximately 2 minutes, according to the satellite velocity of 8 km/s, the horizontal spatial scale was 900 km. Along with the satellite monitoring of the ionosphere over seismically active regions, the behavior of the electric field on the Earth's surface before earthquakes is analyzed [Vershinin et al, 1999;Hao et al, 1998;2000;Rulenko, 2000;Smirnov, 2020]. It was shown that during the preparation of an earthquake, short local bursts of an electric field of large amplitude up to several kV/m with a duration of a few to tens of minutes occur.…”
Section: Analysis Of Results Of Observations Of the Electric Field In...mentioning
confidence: 99%
“…In the chemical pathway, the main factors influencing the lithosphere and near-surface atmosphere are radon gas and changes in the atmospheric electric field. Previous studies have suggested that there is a potential correlation involving heightened radon gas emissions, anomalies in atmospheric electric fields, and the incidence of earthquakes [57,58]. Therefore, the data of radon gas and the atmospheric electric field were also collected, and we sought to explore the linkage between them and the extracted ionospheric TEC disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…Salah satu metode yang dapat digunakan untuk mengamati prekursor gempa bumi adalah melalui pengamatan emisi elektromagnetik (EM) dari litosfer (Hayakawa & Hobara, 2010). Aktivitas seismik sebelum terjadi gempa bumi ditandai dengan adanya anomali medan magnetik serta kerapatan elektron (De Santis, dkk, 2019), dan/atau anomali gradien potensial medan listrik (Smirnov, 2020). Emisi EM sebelum gempa bumi terjadi berada pada rentang frekuensi hertz hingga megahertz (Mullayarov, dkk, 2014) (Petraki, dkk, 2015) (Zhima, dkk, 2020).…”
Section: Pendahuluanunclassified